1990
DOI: 10.1111/j.1095-8649.1990.tb05890.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the host resistance of Atlantic salmon, Salmo salar L., stocks to the monogenean Gyrodactylussalaris Malmberg, 1957

Abstract: The susceptibility and resistance of hatchery‐reared salmon parr, native to the rivers Neva (U.S.S.R. Baltic Sea), Alta (northern Norway) and Lone (western Norway) (both eastern Atlantic Ocean), to Gyrodactylus salaris from Norway, was examined. The level of resistance to the parasite was assessed from counts, made on anaesthetized salmon, ofthe numbers of G. salaris after an initial experimental exposure (2 weeks) to G. salaris‐infected salmon. Three experiments, all in water at c. 12° C, were carried out: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 15 publications
5
84
0
Order By: Relevance
“…In contrast, a range of East Atlantic strains of salmon are highly susceptible and do not activate effective anti-parasitic responses against this particular parasite (Bakke et al 1990, Bakke & MacKenzie 1993, Malmberg 1993, Dalgaard et al 2003, Heinecke & Buchmann 2006, Lindenstrøm et al 2006. The response patterns of fish against gyrodactylids can be divided into 3 groups: (1) innately resistant, (2) susceptible but finally responding and (3) susceptible with no activation of responses (Bakke et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a range of East Atlantic strains of salmon are highly susceptible and do not activate effective anti-parasitic responses against this particular parasite (Bakke et al 1990, Bakke & MacKenzie 1993, Malmberg 1993, Dalgaard et al 2003, Heinecke & Buchmann 2006, Lindenstrøm et al 2006. The response patterns of fish against gyrodactylids can be divided into 3 groups: (1) innately resistant, (2) susceptible but finally responding and (3) susceptible with no activation of responses (Bakke et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Hansen et al (2002), who predicted that local adaptations are most likely to be found at the level of several river systems rather than at the scale of individual rivers unless selection is very strong. The demonstration of differences in susceptibility to specific parasites among wild populations of salmonids (Bakke et al, 1990(Bakke et al, , 2004Dalgaard et al, 2003) as well as other species of teleost fishes (Gleeson et al, 2000;Kalbe and Kurtz, 2006) suggests that local parasite and pathogen faunas exert a significant selective pressure on wild populations and that local adaptation to parasite faunas might be expected at the larger geographical scale. Indeed, Hansen et al (2007) found temporally stable and possibly adaptive divergence at a MHC class I-linked microsatellite locus between two Norwegian brown trout populations suggesting that these populations are locally adapted at MHC loci.…”
Section: Geographical Patterns Of Selectionmentioning
confidence: 99%
“…G. salaris has since been recorded from an additional 45 Norwegian rivers and the parasite is considered to be a major threat to natural Atlantic salmon stocks in Norway (Anonymous 1999). It is now a widely accepted theory that G. salaris was introduced to Norway sometime in the early 1970s and spread through anthropogenic stocking of rivers with infected hatchery-reared juvenile salmon (Johnsen & Jensen 1986, Bakke et al 1990, Hansen et al 2003.…”
Section: Introductionmentioning
confidence: 99%